New role for an old acquaintance: miR-1246 as a new inflammatory and prognostic marker in polytrauma patients - Liudmila P. Leppik; Melissa Manamayil; Cora Schindler; Ramona Sturm; Philipp Störmann; Dirk Henrich; Ingo Marzi; Birte Weber (PeerJ)
Background Based on a literature analysis, we hypothesized that miR-1246 has a high potential as new biomarker after trauma. This miRNA is already established in oncology but has not yet been described in polytrauma. Methods Plasma samples from polytraumatized patients with an ISS ≥ 16 were collected in the emergency room (ER) and 48 hours after trauma. The patients were divided into two groups: a group affected by polytrauma with a leading traumatic brain injury (TBI) (abbreviated injury scale head, AIShead > 4) and a group with a polytrauma without TBI (AIShead = 0). The expression of miR-1246 was measured using qRT-PCR in plasma and plasma extracellular vesicles (EVs). Lastly, we isolated CD171 + EVs by using a magnetic bead-based method and measured miR-1246 expression. Results In plasma, there was a significant increase in miR-1246 in the ER in polytrauma patients, but not in TBI patients. The EV miRNA expression was also significantly increased in the ER samples of the polytrauma patients (*p ≤ 0.0001), while an increase in the expression in the TBI patients (*p ≤ 0.01) was only observed after 48 hours. The systemic expression of miR-1246 correlated with the Injury Severity Score (ISS), creatine kinase and creatinine kinase MB (CK-MB), myoglobin, Interleukin (IL)-6 and the length of hospital stay. In CD171+neuro-EVs, the miR-1246 expression was also significantly increased. Conclusion MiR-1246 was shown to be a marker for the patients’ injury severity, the early inflammatory phase and the patients’ outcome.